Teaching Short Story through Critical Thinking (CT) Strategies - Thapaliya, Mukti Prakash (Journal of NELTA, 2013)
This paper is an attempt to reveal the effectiveness of Critical Thinking (CT) strategies in teaching English literature in general and short stories in particular. Critiquing against the conventional teacher dominated practices in English Language Teaching (ELT) in Nepal, this also offers a set of critical thinking strategies in order to make it more participatory and effective. This heavily draws on my experience of exploiting those techniques while teaching short stories in EFL/ESL classroom in Nepal. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 93-103 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8101